Study protocol: first nationwide comparative audit of acute lower gastrointestinal bleeding in the UK. Issue 8 (4th August 2016) - Oakland, Kathryn; Guy, Richard; Uberoi, Raman; Seeney, Frances; Collins, Gary; Grant-Casey, John; Mortensen, Neil; Murphy, Mike; Jairath, Vipul
Abstract : Introduction: Acute lower gastrointestinal bleeding (LGIB) is a common indication for emergency hospitalisation worldwide. In contrast to upper GIB, patient characteristics, modes of investigation, transfusion, treatment and outcomes are poorly described. There are minimal clinical guidelines to inform care pathways and the use of endoscopy, including (diagnostic and therapeutic yields), interventional radiology and surgery are poorly defined. As a result, there is potential for wide variation in practice and clinical outcomes. Methods and analysis: The UK Lower Gastrointestinal Bleeding Audit is a large nationwide audit of adult patients acutely admitted with LGIB or those who develop LGIB while hospitalised for another reason. Consecutive, unselected presentations with LGIB will be enrolled prospectively over a 2-month period at the end of 2015 and detailed data will be collected on patient characteristics, comorbidities, use of anticoagulants, transfusion, timing and modalities of diagnostic and therapeutic procedures, clinical outcome, length of stay and mortality. These will be audited against predefined minimum standards of care for LGIB. It is anticipated that over 80% of all acute hospitals in England and some hospitals in Scotland, Wales and Northern Ireland will participate. Data will be collected on the availability and organisation of care, provision of diagnostic and therapeutic GI endoscopy, interventional radiology, surgery and transfusion protocols. Ethics and dissemination: This audit will be conducted as part of the national comparative audit programme of blood transfusion through collaboration with specialists in gastroenterology, surgery and interventional radiology. Individual reports will be provided to each participant site as well as an overall report and disseminated through specialist societies. Results will also be published in peer-reviewed journals. The study has been funded by National Health Services (NHS) Blood and Transplant and the Bowel Disease Research Foundation and endorsed by the Association of Coloproctology of Great Britain and Ireland.